A toxicology-informed, safer by design approach for the fabrication of transparent electrodes based on silver nanowires. Issue 2 (20th December 2018) - Toybou, Djadidi; Celle, Caroline; Aude-Garcia, Catherine; Rabilloud, Thierry; Simonato, Jean-Pierre
Abstract : A safer by design approach is demonstrated for the synthesis and integration of silver nanowires into commercial devices. Abstract : Fabrication of silver nanowires (AgNWs) with fine and independent control of both the diameter (from 30 to 120 nm) and length (from 5 to 120 μm) by concomitant addition of co-nucleants and temperature control is demonstrated, and used for the preparation of size standards. Percolating random networks were fabricated using these standards and their optoelectronic properties were measured and compared with regard to the nanowire dimensions. The transparent electrodes appear suitable for various applications and exhibit excellent performances ( e.g. 16 ohm sq −1 at 93% transparency), with haze values varying from 1.6 to 26.2%. Besides, in vitro toxicological studies carried out on murine macrophages with the same size standards revealed that AgNWs are weakly toxic (no toxicity observed below 50 μg mL −1 Ag), in particular compared to other silver nanoparticles. Short AgNWs (4 μm) appeared to be slightly more toxic than longer AgNWs (10 and 20 μm). Conversely, long AgNWs (20 μm) induced a more prolonged pro-inflammatory response in murine macrophages. These results contribute, in a safer by design approach, to promoting the use of short AgNWs. The global knowledge dealing with the combination of nanowire dimensions associated with optoelectronic performances and related toxicity should encourage the rational use of AgNWs, and guide the choice of the most adequate AgNW dimensions in an integrated approach.